PENERAPAN METODE MAKE AND MATCH DAPAT MENINGKATKAN KEAKTIFAN BELAJAR SOSIOLOGI PADA SISWA KELAS X3 SMA NEGERI 1 GUNUNG TULEH KABUPATEN PASAMAN BARAT - renywaty renywaty (JURNAL MANAJEMEN PENDIDIKAN, 2017)
AbstractSociology is one of the subjects that could make people understand themselves and their surroundings, that foster the harmony of life and have a good mental to carry out positive activities.The research objective of this class action is to enhance the activity of studying Sociology in class X SMAN 1 Gunung Tuleh West Pasaman using the Make and Match. This classroom action research conducted in SMA Negeri 1 Mount Tuleh West Pasaman in class X in Ganji semester of academic year 2014/2015. Number of students 30 people.Discussion involving undertaken by students to run well and smoothly, as shown in observations of students in the group collaborative activities "make and match" with the average percentage in the first cycle by 50%. While in the second cycle increased, namely to 73.1%. So cooperation has included students in the group is good.The evaluation results indicate that the bulls are thoroughly studied of 11 students (36.67%) in the pre-action to 18 students (60%) in the first cycle, and to 24 students (80%) in the second cycle. While that has not been thoroughly studied decreased from 19 students (67.33%) in the pre-action, to 12 students (40%) in the first cycle, and being 6 students (20%) in the second cycle.The hypothesis of action which states that "if the Make and Match methods used in learning, the activity of learning the lessons of Sociology at X3 grade students SMA N 1 Mount Tuleh, West Pasaman will increase", is acceptable.This study also provides recommendations to the teachers to be more active and creative in choosing methods of teaching and learning activities in order to improve student achievement. The Principal shall be able to take the policy on the need to implement the Action Research (PTK) for each teacher, so that students' motivation have also increased. Keywords: Methods Make and Match, activeness Learning, and Sociology.